Did our species evolve in subdivided populations across Africa, and why does it matter? - Scerri, EML; Thomas, MG; Manica, A; Gunz, P; Stock, JT; Stringer, C; Grove, M; Groucutt, HS; Timmermann, A; Rightmire, GP; d'Errico, F; Tryon, CA; et al. (Elsevier, 2018)
We challenge the view that our species, Homo sapiens, evolved within a single population and/or region of Africa. The chronology and physical diversity of Pleistocene human fossils suggest that morphologically varied populations pertaining to the H. sapiens clade lived throughout Africa. Similarly, the African archaeological record demonstrates the polycentric origin and persistence of regionally distinct Pleistocene material culture in a variety of paleoecological settings. Genetic studies also indicate that present-day population structure within Africa extends to deep times, paralleling a paleoenvironmental record of shifting and fractured habitable zones. We argue that these fields support an emerging view of a highly structured African prehistory that should be considered in human evolutionary inferences, prompting new interpretations, questions, and interdisciplinary research directions.